Labeling design effort for household refrigerator-freezers in Malaysia - Saidur, Rahman; Masjuki, Haji Hassan; Mahlia, T.M.I. (Energy Policy, 2005)
The paper is particularly concerned with developing a proposed energy guide label for household refrigerator-freezers through consumer research. Survey work conducted throughout Malaysia to develop a comprehensive energy guide label. A simple labeling design with different features and colors was also performed using the labeling concept of other countries (such as Australia, Thailand, and from the EU). There are many steps to implement a labeling program for a particular energy consuming appliance, such as consumer/ stakeholder involvement, design, policy makers' involvement and so on. So, this is a vast area of work. This paper mainly focuses on consumer research in designing or shaping a comprehensive label.